2014
DOI: 10.3389/fcimb.2014.00123
|View full text |Cite
|
Sign up to set email alerts
|

Glycosaminoglycans analogs from marine invertebrates: structure, biological effects, and potential as new therapeutics

Abstract: In this review, several glycosaminoglycan analogs obtained from different marine invertebrate are reported. The structure, biological activity and mechanism of action of these unique molecules are detailed reviewed and exemplified by experiments in vitro and in vivo. Among the glycans studied are low-sulfated heparin-like polymers from ascidians, containing significant anticoagulant activity and no bleeding effect; dermatan sulfates with significant neurite outgrowth promoting activity and anti-P-selectin from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 34 publications
0
41
0
Order By: Relevance
“…The composition of natural physiological HS chains can be altered in several pathological conditions [8][9][10][11]. Heparin and HS-like glycosaminoglycans (GAGs) have been isolated from avian intestinal mucosa [12], terrestrial invertebrates [13,14], marine crustacean and mollusk species [15][16][17] as well as bacterial and virus species [12]. In the Golgi compartment of all animal cells and mast cells of connective tissue, biosynthesis of HS and heparin chains, respectively are completed through common steps leading to the formation of a specific tetrasaccharidic linkage region…”
Section: Heparan Sulfatementioning
confidence: 99%
See 1 more Smart Citation
“…The composition of natural physiological HS chains can be altered in several pathological conditions [8][9][10][11]. Heparin and HS-like glycosaminoglycans (GAGs) have been isolated from avian intestinal mucosa [12], terrestrial invertebrates [13,14], marine crustacean and mollusk species [15][16][17] as well as bacterial and virus species [12]. In the Golgi compartment of all animal cells and mast cells of connective tissue, biosynthesis of HS and heparin chains, respectively are completed through common steps leading to the formation of a specific tetrasaccharidic linkage region…”
Section: Heparan Sulfatementioning
confidence: 99%
“…The highly sulfated domains (NS), constituted by sequences of the trisulfated disaccharide 4-O-L-IdoA2S 1α-4-O-D-GlcNS6S are prevalent in heparin chains, while in the N-acetylated domains (NA), the disaccharide 4-O-α-D-GlcA-1β-4-O-D-GlcNAc) is more abundant in HS chains. NS and NA domains in both HS and heparin are disseminated among mixed transition regions (NS/NA) [9][10][11][12][13][14][15][16][17][18].…”
Section: Heparan Sulfatementioning
confidence: 99%
“…Glycosaminoglycans (GAGs), including heparin-like polymer, that are derived from vertebrates have diverse pharmacological activities including anticoagulant, antithrombotic, and anti-inflammatory activities [1]. GAGs isolated and purified from various vertebrate and invertebrate tissues have been shown to comprise of an anion sugar sulfate with functional properties [2].…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al, (2016a) showed that RNAi silencing of AAS19 caused deformities in ticks suggesting that this serpin regulated an important protease in the tick. There is evidence that invertebrates do produce heparin-like GAGs (Chavante et al, 2014; Pavão, 2014). It will be interesting to investigate if tick derived GAGs affected inhibitory functions of native AAS19 in the tick.…”
Section: Discussionmentioning
confidence: 99%